2018
DOI: 10.1096/fj.201802037r
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for functional interactions between the placenta and brain in pregnant mice

Abstract: The placenta plays a pivotal role in the development of the fetal brain and also influences maternal brain function, but our understanding of communication between the placenta and brain remains limited. Using a gene expression and network analysis approach, we provide evidence that the placenta transcriptome is tightly interconnected with the maternal brain and fetal brain in d 15 pregnant C57BL/6J mice. Activation of serotonergic synapse signaling and inhibition of neurotrophin signaling were identified as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 86 publications
3
44
0
Order By: Relevance
“…In women, altered or failed endometrial decidualization is an essential contributor to later pregnancy complications, such as preeclampsia and pregnancy loss (13), and may be involved in fetal growth restriction and preterm labor (56)(57)(58). Recent evidence supports the idea that GE-derived factors regulate stromal cell decidualization and placental growth in mice (2,59) and humans (8)(9)(10)60). In the present study, we identified many potential FOXA2-regulated genes in the MS phase that encode secreted ligands with receptors on decidualized stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…In women, altered or failed endometrial decidualization is an essential contributor to later pregnancy complications, such as preeclampsia and pregnancy loss (13), and may be involved in fetal growth restriction and preterm labor (56)(57)(58). Recent evidence supports the idea that GE-derived factors regulate stromal cell decidualization and placental growth in mice (2,59) and humans (8)(9)(10)60). In the present study, we identified many potential FOXA2-regulated genes in the MS phase that encode secreted ligands with receptors on decidualized stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…The gene expression of the GD4 maternal brain (MB4) from the present study was compared with the gene expression data of the GD15 maternal brain (MB15) from our previous study (Behura, Kelleher et al, 2019). From this comparison based on the edgeR‐robust analysis (Zhou, Lindsay, & Robinson, 2014), we identified a total of 3,066 genes that showed significant changes (false discovery rate [FDR] p < .05) in expression level in MB15 compared with MB4 (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…The neuroendocrine signaling modulates the maternal–fetal communication, development of the placenta and fetus, and the timing of parturition (Brüning et al, 2000; Mastorakos & Ilias, 2003). These processes are influenced by hormonal interaction between the brain and reproductive organs (Barth, Villringer, & Sacher, 2015; Behura, Dhakal et al, 2019; Behura, Kelleher, & Spencer, 2019; Christensen et al, 2012; Gorski, 1979). The maternal brain (MB) regulates the production of estrogen, progesterone, prolactin, and oxytocin that play important roles in pregnancy (Hillerer, Jacobs, Fischer, & Aigner, 2014; Kim & Strathearn, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations